Percepción de la calidad del servicio al cliente del parque cementerio Jardines del Edén Iquitos junio 2022 - Arevalo Vela, Raquel Rebecca (2023)
The research perception of the quality of customer service of the Gardens the Eden de Iquitos cemetery park as of June 2022, aims to analyze the quality of service perceived by customers of the Gardens the Eden Iquitos cemetery park, June 2022; The work is of a descriptive level with a quantitative approach of non-experimental design and transectional cut, the sample consisted of 340 clients, which includes clients of burials in the ground and burials in niches. The results indicate in general terms the quality of the service throughout the cemetery park is good at 73.82%; In the ground burial service, the quality of the service is rated as good by 79% of those surveyed and in the niche burial service, 63.19% of the clients rated it as good. All the dimensions of service quality have a good rating greater than 60%, with the lowest rating of good being the trust dimension with 62.94% and the dimension with the best rating of good is the dimension of empathy followed by the dimension security with 75.88%